PENERAPAN MODEL STUDENT TEAM ACHIEVMENT DIVISION (STAD) DALAM PEMBELAJARAN SENI TARI KELAS VIII SMP NEGERI 03 MUKOMUKO - Ayu Puspita Sari; Fuji Astuti; Zora Iriani (SENDRATASIK UNP, 2018)
Abstract This research aimed to describe the implementation of Student Team Achievement Division (STAD) model on Dance subject at VIII grade of SMP 03 Mukomuko.This research was classroom action research. The object of the research was 25 students of VIIIA class of SMP 03 Mukomuko. The research instrument was the researcher herself and additional instruments were observation sheet and test. The data were attained through library research, observation, documentation, performance test. Then, the data were analyzed.The result showed that the implementation of STAD model on Dance subject at SMP 03 Mukomuko in cycle 2 ran well. Students were motivated in learning in every cycle. The indicators were paying attention to teacher’s explanation, doing group discussion, expressing opinion, spirit of learning, and good movement. Students learning activity in meeting I of cycle 1 was 49.5%, in meeting II was 61% and in meeting I, cycle 2 was 77%. The average score increased from 71 to 80 as it was “very good” and passed the minimum achievement criteria. In short, STAD model was very effective to improve students’ curiosity and made fun learning so that students’ activity and learning result also increased.Keywords: Application Model STAD, Learning Dance, Junior High School Students